Rathbourney church, east window, jamb - O'Donovan, Danielle (My University, 2008)
Twin ogee headed lights under a square label. Jamb moulding comprises, from intrados: hollow chamfer, right-angled rebate, quadrant, right-angled rebate, ogee.
East window
Keywords: quadrant; Architecture, Gothic -- Ireland; Clare (Ireland)--Antiquities.; Late Medieval; moldings, ogee; moldings, hollow; roll moldings